Murder at the book group [large type] - King, Maggie, 1950- (Thorndike Press large print mystery series., 2015)
Hazel Rose never dreamed that the murder mystery book group she and her friend Carlene started would stage a real murder. How much does anyone really know about Carlene Arness? And did she die by her own hand or someone else's? Hazel begins a search for the truth that produces no shortage of motives, as she unearths the past that Carlene took great pains to hide. And most of those motives belong to the members of her very own book group.